High prevalence and little awareness in patients with chronic inflammatory skin diseases and genital involvement. (16th August 2021) - Staubach, Petra; Plavic‐Radeka, Natascha; Peveling‐Oberhag, Adriane; Sohn, Anna; Zimmer, Sebastian; Weyer‐Elberich, Veronika; Lang, Berenice Mareen
Summary: Background: Genital involvement in patients with chronic inflammatory skin diseases is frequent, yet insufficiently acknowledged. Objective: To evaluate the prevalence of genital symptoms in psoriasis and chronic urticaria patients, effects on quality of life, physician‐patient relations and disease management. Patients and Methods: 100 patients with psoriasis and 100 with chronic urticaria from our outpatient clinic, as well as 50 healthy controls were included. Data was collected using questionnaires developed by dermatological experts. Results: Out of 250 subjects, 74 % had already experienced genital symptoms – 70 % of psoriasis patients and 58 % of urticaria patients. Seven out of ten even complained about recurrent genital involvement. 50 % of psoriasis and 41 % of urticaria patients reported an impact on quality of life. 41 % identified genital pruritus as the main symptom, with one out of three expecting a better management for this specific problem. Furthermore, 74 % complained about a lack of awareness among physicians: 79 % of urticaria patients and 58 % of psoriasis patients reported never having been questioned about genital symptoms by their physicians. Conclusions: The majority of patients with psoriasis and chronic urticaria suffer from genital involvement and an impaired quality of life. Patient and physician reported outcomes should include genital symptoms as an influencing factor for quality of life.